2009
DOI: 10.1002/jhet.81
|View full text |Cite
|
Sign up to set email alerts
|

New dihydro‐1,2,4‐triazolo[1,5‐a]pyrimidines based on arylidene derivatives of 5‐acetylbarbituric and dehydroacetic acids

Abstract: in Wiley InterScience (www.interscience.wiley.com).The reaction of 3-amino-1,2,4-triazole (1) with arylidene-5-acetyl barbituric acid (2b,c) or dehydroacetic acid (2a) by refluxing in butanol leads to the formation of dihydro-1,2,4-triazolo[1,5-a]pyrimidines 3a-c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The 1 H NMR spectra of crownophane 7 are character ized by an unusually high field shifts for the protons H (20) and H(5) in the region δ 3.16 and 5.59, respectively (Fig. 6), that is explained by the shielding effect of the triazolo pyrimidine ring.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The 1 H NMR spectra of crownophane 7 are character ized by an unusually high field shifts for the protons H (20) and H(5) in the region δ 3.16 and 5.59, respectively (Fig. 6), that is explained by the shielding effect of the triazolo pyrimidine ring.…”
Section: Resultsmentioning
confidence: 98%
“…6), that is explained by the shielding effect of the triazolo pyrimidine ring. According to the X ray diffraction data, the distances between the hydrogen atom H (20) and H (5) and the plane of the condensed ring are 2.25 and 2.40 Å, respectively, and these both atoms are placed inside the cone of magnetic anisotropy. It is probable, that this con formation is also preserved in solution, that is confirmed by the presence of the cross peak between the H(5) and H(2) in the 1 H-1 H NOESY 2D spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 Their simultaneous formation (TLC data) together with the [1,5 a] isomers indicated that the reaction took the Michael addition direction, rather than the Dimroth rear (2) ( [1 -x, 1 -y, 1 -z]) with the distance of 2.38 Å, according to the X ray diffraction data. (7) O (1) С (8) С (9) С (10) С (11) O (2) С (12) С (13) С (14) С (15) С (16) С (17) С (1) С (2) O (1) С (6) С (7) С (8) С (9) С (10) С ( rangement usually occurring in acidic media. According to the X ray diffraction data, the molecular packing of 5d is composed of molecules of two conformers A and B (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 and their synthetic analogs, are important compo nents not only in the reactions dealing with the generation of optical centers, 2,3 but, first of all, in the synthesis of various heterocyclic systems, 4,5 including azoloazines. [6][7][8][9][10] Functionalization of chalcones with the oligooxyethyl ene fragment on going to their macrocyclic analogs (for example, diarylideneacetonyl crownophane) and acyclic chalconopodands 11-13 can considerably broaden chemi cal potential of , unsaturated carbonyl compounds in the synthesis of alkaloid like structures, including crown ether derivatives. In our studies of the reactions of chalco nopodands with nucleophiles, including aminoazoles, we found that a bulky substituent (a polyether chain) played a significant role in the approaching reaction centers of molecules and direction of cascade reactions, leading to the formation of several C-C and C-N bonds of poly cyclic system, [14][15][16] in one (one pot) reaction cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Azolopyrimidines having a nodal nitrogen are excellent objects for both, either multicomponent [2] or sequential synthesis [3] (Scheme 1); both of them presume use of diverse aminoazoles 1 (3-amino-1,2,4-triazole [4], 3-aminopyrazole [5], 5-aminotetrazole [6] Another important trend in modern synthesis is "green chemistry" [7]; among its principles use of "green" solvents like water appeared to be highly effective [8].…”
Section: Introductionmentioning
confidence: 99%